Preparation of cerium-doped surface modified activated carbon and application of cerium-doped surface modified activated carbon in perfluorinated compound adsorption
Through the preparation of cerium-doped surface modified activated carbon, the problem of low efficiency of traditional activated carbon when removing perfluoro compounds in water is solved, and efficient, stable and economical wastewater treatment is achieved, which is suitable for the treatment of multiple types and high concentration wastewater.
Patent Information
- Application Number
- CN202411440592.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Traditional activated carbons have low removal efficiency when removing perfluoro compound PFOA in water, and prior art such as biological treatment and advanced oxidation techniques can produce highly toxic intermediates or consume high energy and have complex operations, which limits their large-scale applications.
Through the preparation of cerium-doped surface modified activated carbon, hydrothermal reaction and calcination treatment with activated carbon by cerium salt, citric acid and NaOH, the specific surface area of the material and the adsorption active site are significantly increased, and the adsorption performance and efficiency are improved.
It has achieved efficient removal of perfluoro compounds in water, especially suitable for treating high concentration wastewater, reducing the risk of secondary pollution, high material stability, suitable for long-term applications and low preparation cost.
Smart Images

Figure CN119186533A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental governance, and specifically relates to the preparation of cerium-doped surface-modified activated carbon and its application in adsorbing perfluorinated compounds. Background Art
[0002] With the advancement of industrialization and urbanization, environmental problems are becoming increasingly severe, and various newly detected difficult-to-degrade trace pollutants are emerging in an endless stream, bringing new pressure to our governance of environmental pollution. Perfluorinated compounds are typical representatives of them. Perfluorinated compounds refer to a class of organic compounds in which all hydrogen atoms connected to carbon atoms in the compound are replaced by fluorine atoms. They are widely used in non-stick products, foam fire extinguishing agents and electronic manufacturing due to their extremely strong thermal stability, chemical stability and surface activity. Among them, perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) have the largest output and the widest application. Due to the high stability of the CF long chain, this type of compound is difficult to be naturally degraded, which is easy to cause a lasting impact on the environment. As a typical representative, perfluorooctanoic acid (PFOA) has attracted much attention from the society due to its persistence and high toxicity. It has been defined as a new persistent organic pollutant (POPs) and has been included in the Stockholm Convention priority list. However, due to its extensive application in the past few decades, PFOA has been widely present in a variety of environmental media, which makes the governance of PFOA a huge challenge for us from the environment. At the same time, PFOA can enter human blood through the food chain, thus having adverse effects on human growth and development, which makes the control of PFOA not to be ignored and urgent. Therefore, the research on PFOA removal technology has become a hot issue that cannot be avoided in the environmental field.
[0003] Although many treatment technologies have been used to remove PFOA, including biological treatment technology, advanced oxidation technology and thermal degradation technology. However, biological treatment technology and advanced oxidation technology will produce a large number of highly toxic intermediates in the process of treating PFOA, causing secondary pollution; thermal degradation technology has high energy consumption, complex operation and harsh reaction conditions. It is these limitations that hinder the large-scale application of these new technologies. The adsorption method is expected to become the best technology for removing PFOA due to its advantages such as low cost, simple design, good effect, no by-products during adsorption, and the ability to remove pollutants adsorbed on the adsorbent during regeneration. At present, activated carbon adsorption is the most widely used adsorption method for removing PFOA from water, but traditional activated carbon only relies on physical adsorption to eliminate PFOA, and the removal efficiency is very low. Therefore, it is of great significance to develop new activated carbon adsorbents with high removal efficiency. Summary of the invention
[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present invention modifies the surface of activated carbon by doping with cerium, thereby increasing the contact area between the AC material and the pollutants, improving the adsorption performance and adsorption efficiency of the material, and enabling it to efficiently remove perfluorinated compounds in water.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a method for preparing cerium-doped surface-modified activated carbon, the method comprising the following steps:
[0007] S1. dissolving cerium salt and citric acid in water to form a transparent solution, then adding NaOH and activated carbon, and performing a hydrothermal reaction;
[0008] S2. After the reaction, the mixture is cooled to room temperature, and the solids after the reaction are collected, washed and dried, and then transferred to an inert gas atmosphere for calcination to obtain a finished product.
[0009] The synthesis process of the material is simple, with few steps and easy operation, and the preparation cost is low, making the production process economical and efficient. The preparation conditions are low, and no high-precision equipment or extreme operating conditions are required, which is conducive to large-scale production.
[0010] Preferably, the mass ratio of the cerium salt, citric acid, NaOH and activated carbon is 140-160:20-30:13-19:900-1100.
[0011] Preferably, the temperature of the hydrothermal reaction is 150-250° C. and the time is 20-30 hours.
[0012] Preferably, the cerium salt includes cerium chloride, cerium nitrate, and cerium sulfate.
[0013] Preferably, the calcination temperature is 500-900°C, the time is 1-3h, and the heating rate is 8-12°C / min.
[0014] The second aspect of the present invention provides cerium-doped surface-modified activated carbon prepared by the preparation method described in the first aspect.
[0015] The third aspect of the present invention provides the use of the cerium-doped surface-modified activated carbon described in the second aspect in the adsorption of perfluorinated compounds.
[0016] The modified activated carbon synthesized by the method of the present invention has high adsorption performance, can efficiently remove perfluorinated compounds in water, and is particularly suitable for treating multi-type, high-concentration wastewater. At the same time, it can effectively prevent secondary pollution. During the treatment process, the pollutants are effectively enriched on the surface of the material, which is helpful for subsequent further treatment and reduces the risk of secondary pollution. In addition, the adsorbent can be reused and is easy to regenerate without a complicated regeneration process, which reduces maintenance costs and operational complexity and is suitable for long-term application.
[0017] Preferably, the perfluorinated compound is perfluorooctanoic acid (PFOA).
[0018] Preferably, the specific application method is: putting the cerium-doped surface-modified activated carbon described in claim 6 into a water body containing perfluorinated compounds and adsorbing it for more than 30 minutes.
[0019] More preferably, the input amount of cerium-doped surface-modified activated carbon is 5-10 mg / 100 mL.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention discloses a method for preparing cerium-doped surface-modified activated carbon, which comprises dissolving cerium salt and citric acid in water to form a transparent solution, then adding NaOH and activated carbon, and then sequentially subjecting the solution to hydrothermal reaction and calcination. The modified activated carbon synthesized by the method of the present invention has high-efficiency adsorption performance and significantly improved specific surface area, thereby increasing the contact area between the AC material and the pollutants, and greatly improving the adsorption performance and adsorption efficiency of the material, so that the material can efficiently remove perfluorinated compounds in water, and is particularly suitable for treating multi-type, high-concentration wastewater. In general, the present invention has the following advantages:
[0022] (1) Significantly increased specific surface area: Compared with traditional activated carbon adsorbents, the cerium-doped activated carbon adsorbent of the present invention significantly increases the specific surface area of the material through optimized preparation process and cerium doping. This feature enables more pollutants to be effectively contacted and adsorbed, improving the overall treatment capacity and efficiency.
[0023] (2) Increased adsorption active sites: Cerium doping improves the microstructure of activated carbon and increases the adsorption active sites. This structural improvement not only improves the adsorption capacity of target pollutants, but also enhances the selectivity of the adsorbent, enabling it to more efficiently remove different types of pollutants in wastewater.
[0024] (3) Improved adsorption performance and rate: Thanks to the increase in specific surface area and active sites, the adsorbent of the present invention exhibits excellent adsorption performance and faster treatment rate during wastewater treatment. Compared with existing activated carbon adsorbents, the present invention can achieve higher removal efficiency in a shorter time, significantly improving the rate and effect of wastewater treatment.
[0025] (4) Significantly improved material stability: Cerium-doped activated carbon exhibits excellent chemical and physical stability during use and can maintain efficient adsorption performance during long-term operation. Compared with existing activated carbon adsorbents, the adsorbent of the present invention is less likely to experience performance degradation during the treatment process, reducing replacement frequency and maintenance costs.
[0026] (5) Wide applicability: The cerium-doped activated carbon adsorbent of the present invention can effectively treat wastewater of various types and concentrations, especially when treating wastewater containing perfluorinated compounds, showing more excellent performance. This wide applicability enables the adsorbent to meet the wastewater treatment needs of different industrial and environmental fields and has a wider application potential.
[0027] (6) Low cost and simple preparation process: The cerium-doped activated carbon adsorbent of the present invention has low preparation cost, simple preparation process and low requirements on conditions. This advantage makes the adsorbent more economical and production feasible, and has significant cost-effectiveness compared with the complex and high-cost preparation process of existing activated carbon adsorbents.
[0028] In summary, the new cerium-doped activated carbon adsorbent prepared by the method of the present invention shows significant advantages in specific surface area, adsorption active sites, adsorption performance, material stability, wide treatment range, reaction conditions, environmental protection and preparation cost, so that it can meet the multiple needs of wastewater treatment for high efficiency, economy and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the full spectrum of X-ray photoelectron spectra of different cerium-doped activated carbon adsorbents;
[0030] Figure 2 X-ray photoelectron spectroscopy Ce 3d spectra of different cerium-doped activated carbon adsorbents;
[0031] Figure 3 The BET results of different cerium-doped activated carbon adsorbents measured by nitrogen adsorption and desorption;
[0032] Figure 4 is the removal rate of PFOA by cerium-doped activated carbon adsorbent at different times;
[0033] Figure 5The removal efficiency of PFOA of different concentrations by cerium-doped activated carbon adsorbent AC-Ce-900 at different times;
[0034] Figure 6 is the removal efficiency of PFOA with different initial pH at different times by cerium-doped activated carbon adsorbent AC-Ce-900;
[0035] Figure 7 is the removal efficiency of PFOA by cerium-doped activated carbon adsorbent AC-Ce-900 in the presence of humic acid (HA) or fulvic acid (FA);
[0036] Figure 8 The removal efficiency of PFOA by cerium-doped activated carbon adsorbent AC-Ce-900 under different coexisting ion conditions;
[0037] Fig. 9 The removal efficiency of PFOA at different temperatures at different times by cerium-doped activated carbon adsorbent AC-Ce-900;
[0038] Fig.10 The removal efficiency of PFOA in different actual water bodies by cerium-doped activated carbon adsorbent AC-Ce-900 at different times. DETAILED DESCRIPTION
[0039] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0040] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0041] Example 1: Preparation of cerium-doped surface-modified activated carbon
[0042] (1) 149.032 mg CeCl3·7H2O and 26.4165 mg citric acid were weighed and dissolved in 80 mL deionized water to form a transparent solution. Then, 16 mg NaOH was added under magnetic stirring, and after stirring for 15 min, 1 g activated carbon was slowly added. The mixture was then transferred to a Teflon-lined autoclave and hydrothermally treated at 200 °C for 24 h.
[0043] (2) After the reaction, the mixture was cooled to room temperature, and the solid was collected by suction filtration. The solid was washed several times with deionized water and dried in an oven at 60° C. overnight to obtain a precursor.
[0044] (3) The precursor was transferred to a tube furnace and calcined at 500°C, 700°C, and 900°C for 2 h under a N2 atmosphere at a heating rate of 10°C / min. The calcined AC-Ce material was then ground into powder to obtain a finished product. The AC-Ce materials obtained at 500, 700, and 900°C were labeled as AC-Ce-500, AC-Ce-700, and AC-Ce-900, respectively.
[0045] Figure 1 The full spectrum of X-ray photoelectron energy spectrum shows that compared with AC before modification, the modified material has a new peak of Ce 3d in the range of 880-910eV, indicating that Ce is successfully doped in the modified material.
[0046] As shown in Table 1 and Figure 2 As shown, the Ce of AC-Ce-900 3+ Higher than Ce 4+ , Ce 3+ The content is about 50.77%, while Ce 4+ The content is about 49.23%. 3+ The content is also higher than Ce 4+ , Ce 3+ The content is about 53.48%, while Ce 4+ The content is about 46.52%. 3+ The content is lower than Ce 4+ , Ce 3+ The content is about 48.64%, while Ce 4+ The content is about 51.36%.
[0047] Table 1 X-ray photoelectron spectroscopy Ce 3d test results of different cerium-doped activated carbon adsorbents
[0048] catalyst <![CDATA[Ce 4+ (%)]]> <![CDATA[Ce 3+ (%)]]> AC-Ce-900 49.23 50.77 AC-Ce-700 46.52 53.48 AC-Ce-500 51.36 48.64 AC 0 0
[0049] As shown in Table 2 and Figure 3 As shown in Figure 2, the introduction of Ce significantly increased the specific surface area of AC. The introduction of Ce and calcination at 900 °C increased the specific surface area of AC from 1131.6 m 2 / g increased to 1431.3m 2 / g, the improvement effect is most obvious.
[0050] Table 2 Nitrogen adsorption and desorption test results of different cerium-doped activated carbon adsorbents
[0051] catalyst AC-Ce-900 AC-Ce-700 AC-Ce-500 AC <![CDATA[BET result (m 2 / g)]]> 1431.3 1400.1 1321.6 1131.6
[0052] Example 2: Investigation of adsorption performance of cerium-doped surface-modified activated carbon
[0053] In order to evaluate the adsorption performance of the new cerium-doped activated carbon adsorbent, the following experiments were conducted:
[0054] (1) 100 mL of 10 mg / L PFOA solution was prepared with 1 g / L perfluorooctanoic acid (PFOA) mother liquor, and the mixture was stirred evenly on a magnetic stirrer at a speed of 520 rpm. Then, 6 mg of the adsorbent material (AC-Ce-500, AC-Ce-700 and AC-Ce-900) prepared in Example 1 was added to the 100 mL PFOA solution for 30 min of adsorption reaction.
[0055] (2) Sampling was performed at 0 min, 10 min, 20 min, and 30 min, and then 1 mL of the sample was taken using a syringe and filtered through a 0.45 μm filter membrane, and then tested using high performance liquid chromatography.
[0056] From Table 3 and Figure 4 It can be seen that AC-Ce-900 has the highest removal efficiency, which can remove 86% of PFOA in 30 minutes. Compared with the activated carbon before modification, the removal efficiency of PFOA is increased by 7.88 times.
[0057] Table 3 Removal efficiency of PFOA by cerium-doped activated carbon adsorbent
[0058] Adsorbent AC AC-Ce-500 AC-Ce-700 AC-Ce-900 PFOA removal rate (%) 10.88 26.98 70.04 85.71
[0059] Example 3: Adsorption performance of cerium-doped surface-modified activated carbon at different initial PFOA concentrations
[0060] In order to evaluate the adsorption performance of the new cerium-doped activated carbon adsorbent AC-Ce-900 at different initial concentrations of PFOA, the following experiments were conducted:
[0061] (1) 100 mL of PFOA solutions with concentrations of 10, 75, and 150 mg / L were prepared with 1 g / L PFOA mother solution and stirred evenly on a magnetic stirrer at a speed of 520 rpm. Then, 6 mg of AC-Ce-900 adsorbent material was added to 100 mL of PFOA solution for 60 min of adsorption reaction.
[0062] (2) Sampling was performed at 0 min, 5 min, 10 min, 15 min, 20 min, 30 min, and 60 min, and 1 mL of the sample was taken using a syringe and filtered through a 0.45 μm polyethersulfone needle filter, and then tested using high performance liquid chromatography.
[0063] From Table 4 and Figure 5It can be seen that with the increase of the initial concentration of PFOA, the adsorption rate gradually decreases, indicating that the adsorption sites of the adsorbent are limited, and with the increase of the initial concentration of PFOA, the adsorption amount gradually increases, indicating that high concentration of pollutants is conducive to promoting the adsorption process towards adsorption saturation.
[0064] Table 4 Removal efficiency of PFOA at different concentrations by cerium-doped activated carbon adsorbent AC-Ce-900
[0065] PFOA concentration (mg / L) Adsorption rate (%) 60min adsorption capacity (mg / g) 10 77.27 128.78 75 26.64 328 150 18.37 459.25
[0066] Example 4: Adsorption performance of PFOA on cerium-doped surface-modified activated carbon at different initial pH values
[0067] In order to evaluate the adsorption performance of the novel cerium-doped activated carbon adsorbent AC-Ce-900 under PFOA at different initial pH, the following experiments were conducted:
[0068] (1) 100 mL of 20 mg / L PFOA solution was prepared with 1 g / L PFOA mother solution, and its initial pH value was adjusted to 3, 5, 7, 9 and 11 respectively using 1 mol / L HCl and NaOH solutions, and then stirred evenly on a magnetic stirrer at a speed of 520 rpm, and then 6 mg of AC-Ce-900 adsorbent material was added to 100 mL PFOA solution for 30 min of adsorption reaction;
[0069] (2) Sampling was performed at 0 min, 5 min, 10 min, 15 min, 20 min, and 30 min, and then 1 mL of the sample was taken using a syringe and filtered through a 0.45 μm polyethersulfone needle filter, and then tested using high performance liquid chromatography.
[0070] from Figure 6 It can be seen that as the initial pH of the solution decreases, the adsorption rate of PFOA by AC-Ce-900 adsorbent gradually increases, indicating that acidic conditions are conducive to the adsorption of PFOA by AC-Ce-900 adsorbent.
[0071] Example 5: Adsorption performance of cerium-doped surface-modified activated carbon under the influence of organic matter
[0072] In order to evaluate the adsorption performance of the new cerium-doped activated carbon adsorbent AC-Ce-900 under the influence of organic matter humic acid (HA) and fulvic acid (FA), the following experiments were conducted:
[0073] (1) 100 mL of a mixed solution was prepared with 1 g / L PFOA mother solution and 2 g / L HA and FA mother solutions, wherein the concentration of HA or FA was 5 mg / L or 10 mg / L, and the concentration of PFOA was 10 mg / L, and then the mixture was stirred evenly on a magnetic stirrer at a speed of 520 rpm, and then 6 mg AC-Ce-900 adsorbent material was added to the 100 mL mixed solution for 30 min of adsorption reaction;
[0074] (2) Sampling was performed at 0 min and 30 min, and then 1 mL of the sample was taken using a syringe and filtered through a 0.45 μm polyethersulfone needle filter, and then tested using high performance liquid chromatography.
[0075] from Figure 7 It can be seen that humic acid (HA) and fulvic acid (FA) have little effect on adsorption, and the presence of 5 mg / L FA will also promote the adsorption of PFOA by AC-Ce-900.
[0076] Example 6: Adsorption performance of PFOA by cerium-doped surface-modified activated carbon under the influence of different coexisting ions
[0077] In order to evaluate the adsorption performance of the new cerium-doped activated carbon adsorbent AC-Ce-900 for PFOA under the influence of different coexisting ions, the following experiments were conducted:
[0078] (1) 100 mL of 10 mg / L PFOA solution was prepared with 1 g / L PFOA mother solution, and then NaCl, Na2SO4, Na2CO3 and NaH2PO4 were added to the solution respectively to form a mixed solution with a coexisting ion concentration of 5 mmol / L, which was then stirred evenly on a magnetic stirrer at a speed of 520 rpm, and then 6 mg of AC-Ce-900 adsorbent material was added to the 100 mL solution for 30 min of adsorption reaction;
[0079] (2) Sampling was performed at 0 min and 30 min, and then 1 mL of the sample was taken using a syringe and filtered through a 0.45 μm polyethersulfone needle filter, and then tested using high performance liquid chromatography.
[0080] from Figure 8 It can be seen that only CO3 2- It will inhibit the adsorption of PFOA by AC-Ce-900 adsorbent, probably because CO3 2- Will hydrolyze to produce OH - , making the solution alkaline and inhibiting the adsorption of PFOA by AC-Ce-900 adsorbent. - It will not affect the adsorption performance of the adsorbent, and SO4 2- and H2PO 4- On the contrary, it will promote the adsorption of PFOA by the material.
[0081] Example 7: Adsorption performance of PFOA by cerium-doped surface-modified activated carbon under the influence of different solution temperatures
[0082] In order to evaluate the adsorption performance of the new cerium-doped activated carbon adsorbent AC-Ce-900 on PFOA under the influence of different solution temperatures, the following experiments were conducted:
[0083] (1) 100 mL of 10 mg / L PFOA solution was prepared with 1 g / L PFOA mother solution, and then stirred evenly on a magnetic heating stirrer at a speed of 520 rpm, and the heating temperatures were set to 25 °C, 35 °C, and 50 °C, respectively. When the solution temperature stabilized, 6 mg of AC-Ce-900 adsorbent material was added to the solution for 30 min of adsorption reaction;
[0084] (2) Sampling was performed at 0 min, 5 min, 10 min, 20 min and 30 min, and then 1 mL of the sample was taken using a syringe and filtered through a 0.45 μm polyethersulfone needle filter, and then tested using high performance liquid chromatography.
[0085] from Fig. 9 It can be seen that as the solution temperature increases, the adsorption amount of PFOA by AC-Ce-900 adsorbent gradually decreases, indicating that the adsorption of PFOA by this material is an exothermic process.
[0086] Example 8: Adsorption performance of PFOA by cerium-doped surface-modified activated carbon in different actual water bodies
[0087] In order to evaluate the adsorption performance of the new cerium-doped activated carbon adsorbent AC-Ce-900 on PFOA in different actual water bodies, the following experiments were conducted:
[0088] (1) Prepare 100 mL of 10 mg / L PFOA solution using deionized water, tap water, river water and seawater respectively, and stir evenly on a magnetic stirrer at a speed of 520 rpm. Then add 6 mg of AC-Ce-900 adsorbent material to the 100 mL PFOA solution and perform adsorption reaction for 30 min.
[0089] (2) Sampling was performed at 0 min, 5 min, 10 min, 20 min and 30 min, and then 1 mL of the sample was taken using a syringe and filtered through a 0.45 μm polyethersulfone needle filter, and then tested using high performance liquid chromatography.
[0090] from Fig.10 It can be seen that different actual water bodies have little effect on the adsorption performance of AC-Ce-900 material, indicating that AC-Ce-900 can be used in actual water bodies to treat PFOA pollutants.
[0091] In summary, the cerium-doped surface-modified activated carbon prepared by the method of the present invention has a significantly improved specific surface area, thereby increasing the contact area between the AC material and the pollutants, and improving the adsorption performance and adsorption efficiency of the material, so that it can efficiently remove perfluorinated compounds in water, and is particularly suitable for treating multiple types of high-concentration wastewater.
[0092] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing cerium-doped surface-modified activated carbon, characterized in that: The following steps are involved: S1. dissolving cerium salt and citric acid in water to form a transparent solution, then adding NaOH and activated carbon, and performing a hydrothermal reaction; S2. After the reaction, the mixture is cooled to room temperature, and the solids after the reaction are collected, washed and dried, and then transferred to an inert gas atmosphere for calcination to obtain a finished product.
2. The method for preparing a cerium-doped surface-modified activated carbon according to claim 1, characterized in that: The mass ratio of the cerium salt, citric acid, NaOH and activated carbon is 140-160:20-30:13-19:900-1100.
3. The method for preparing a cerium-doped surface-modified activated carbon according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 150-250° C. and the time is 20-30 hours.
4. The method for preparing a cerium-doped surface-modified activated carbon according to claim 1, characterized in that: The cerium salt includes cerium chloride, cerium nitrate and cerium sulfate.
5. The method for preparing a cerium-doped surface-modified activated carbon according to claim 1, characterized in that: The calcination temperature is 500-900°C, the time is 1-3h, and the heating rate is 8-12°C / min.
6. Cerium-doped surface-modified activated carbon prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the cerium-doped surface-modified activated carbon according to claim 6 in the adsorption of perfluorinated compounds.
8. The use according to claim 7, characterized in that: The perfluorinated compound is perfluorooctanoic acid (PFOA).
9. The use according to claim 7, characterized in that: The specific application method is: putting the cerium-doped surface-modified activated carbon described in claim 6 into a water body containing perfluorinated compounds and adsorbing for more than 30 minutes.
10. The use according to claim 9, characterized in that: The input amount of cerium-doped surface-modified activated carbon is 5-10 mg / 100 mL.
Citation Information
Patent Citations
Preparation of cerium-doped high-crystallinity carbon nitride adsorbent and application of cerium-doped high-crystallinity carbon nitride adsorbent in adsorption of emerging pollutants
CN115121215A
Application of nano cerium oxide in enhanced pyrolysis of perfluoroalkyl compound
CN117839562A
Compositions and methods for removal of per- and polyfluoroalkyl substances (PFAS)
US20210206670A1
Cited By
Adsorbent material for removing perfluoroalkyl substances and polyfluoroalkyl substances in water and preparation method of adsorbent material
CN122032523A